Lelongan Aset Kereta oleh Firma G-Mart dari Perspektif Islam (Kanun: Jurnal Undang-undang Malaysia, 2012)
This study attempts to compare various practice in the process of the vehicle auction conducted by the G-MART firm in the light of the Syariah law. This study used a qualitative design whereby the data obtained through interviews observations of the firm. The data are then analysed from the perspective of Syariah law. The findings of the study show that the vehicle auction contract as conducted by G-MART which is in full compliance with the guidelines set by law, is also valid and acceptable from the perspective of Islamic law. Further, the current practice of the G-Mart firm fulfils the requirements of the Islamic law, but this has not been adequately highlighted.Keywords: Islamic auction, vehicle auction, bid, Syariah law